Thermal performance enhancement of a cooling tower heat sink radiator. (December 2021) - Mejbil, Hazim Alwan; Jaffal, Hayder Mohammad
Abstract: An experimental study was performed to examine the effect of fin design on the thermal performance of the cooling tower heat sink radiator. The cooling tower heat sink radiator is a new effective heat sink for cooling central processing units using two working fluids, water, and air. By relying on passive heat transfer optimization techniques, two fin designs, namely, truncated and ribbed fins were proposed and tested in comparison with that of traditional flat fins. Tests were conducted for different ranges of air flow Reynolds number (4000–6000), inlet water temperature (310–330 K), and water mass flow rate (0.002–0.01 kg/s). The results revealed that utilizing the truncated and ribbed fins in the heat sink offers better thermal performance than the flat fins. However, it is found that the heat sink with ribbed fins is more effective than that with truncated fins. The improvement in heat transfer in the proposed channels is attributed to the periodic change of the air path and its progressive mixing along the heat channels. The results showed that the average percentage increase in the Nusselt numbers in the truncated and ribbed fins were 1.2 and 1.5, respectively. Highlights: Cooling tower heat sink radiator fin design experimentally analyzed. Two fin designs was proposed and tested; truncated and ribbed fins. Truncated fins can improve the Nusselt number and thermal resistance. The cooling tower heat sink radiator with ribbed fins exhibited the best thermal performance. Cooling energy improvement by up to 61% is achieved with the ribbed fins compared with that with flat fins.